2021
DOI: 10.1002/adfm.202104162
|View full text |Cite
|
Sign up to set email alerts
|

Shining Light on Porous Liquids: From Fundamentals to Syntheses, Applications and Future Challenges

Abstract: Porous liquids (PLs), an emerging type of flowing liquid materials that combine the merits of porous solids and flowing liquids, have garnered immense attention since the concept of PLs was proposed in 2007. Meanwhile, PLs have witnessed growing success in versatile synthesis strategies and emerging applications, especially since 2017. Given the lack of a timely comprehensive review, developing a prompt summary with a comprehensive understanding is undoubtedly urgent. Thus, this critical review offers a compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 304 publications
(422 reference statements)
0
38
0
Order By: Relevance
“… 25 In addition, while the formation of a melt-quenched glass with glass transition was not formally noted, it is also worthwhile to mention that one of the alkylated POCs from the initial type I porous liquid study was reported to also have a glassy appearance, namely the n -octyl decorated POC. 21 …”
Section: Key Milestones In the Development Of Porous Liquidsmentioning
confidence: 99%
See 2 more Smart Citations
“… 25 In addition, while the formation of a melt-quenched glass with glass transition was not formally noted, it is also worthwhile to mention that one of the alkylated POCs from the initial type I porous liquid study was reported to also have a glassy appearance, namely the n -octyl decorated POC. 21 …”
Section: Key Milestones In the Development Of Porous Liquidsmentioning
confidence: 99%
“…25 In addition, while the formation of a melt-quenched glass with glass transition was not formally noted, it is also worthwhile to mention that one of the alkylated POCs from the initial type I porous liquid study was reported to also have a glassy appearance, namely the n-octyl decorated POC. 21 It was not until 2015 that the rst systems formally identied as porous liquids were reported, where both type I and type II porous liquids, based on hollow silica spheres and POCs respectively, were realised. 26,27 Building on the initial attempts at forming porous liquids using POCs, two different strategies were employed to improve their solubility, as opposed to inducing melting, enabling high concentration type II porous liquids to be formed on dissolution in cavity-excluded solvents (Fig.…”
Section: Key Milestones In the Development Of Porous Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalysis by PLs possesses both advantages and can achieve high selectivities for many industrial separations. 125,126 Recently, porous solids have been used to protect catalysts in PL catalysis, as represented in Fig. 9.…”
Section: Practical Applications Of Porous Iquidsmentioning
confidence: 99%
“…Consequently, PLs have shown excellent prospects, especially in gas adsorption, [17][18][19][20][21] separation [22][23][24][25] and catalysis, 26 etc. Until now, PLs based on various types of pore generators and sterically hindered solvents have been successively reported, such as ionic liquid encapsulated nano hollow spheres porous liquid materials, 27 alkyl modified cavity tetrahedral crystal porous liquid materials, 28 porous solid materials dissolved in macromolecular solvents, [29][30][31] and so on. For example, Li reported a new class of PLs using internally functionalized metal-organic framework (MOF) particles as pore generators and polydimethylsiloxane (PDMS) as sterically hindered solvents.…”
Section: Introductionmentioning
confidence: 99%